A CLINICAL-EPIDEMIOLOGICAL STUDY ON BLUNT OCULAR TRAUMA AND ITS VISUAL OUTCOME IN A TERTIARY CARE HOSPITAL OF EASTERN INDIA. - Parida, Shrutakirty; Dash, Snehalata; Sen, Saswati (Student's Journal of Health Research Africa, 2024)
Background: Injury in the ocular region accidental or intended leads to ocular morbidity that accounts for poor visual prognosis and loss of quality of life, if not diagnosed and managed at the earliest. The study aims to observe clinical-epidemiological aspects of blunt ocular trauma and to determine the visual capacity. Methodology: An observational study was conducted. Patients with blunt ocular trauma at tertiary care hospitals were undertaken for the study. Relevant history with demographic data was noted. A detailed clinical and thorough ocular examination was done. Patients were managed with medical or surgical methods and follow-up was taken for the next six months. Results: Blunt ocular trauma, found in 0.24% of cases, primarily affected males aged 21 to 30 years, often laborers, agricultural workers, or rural residents. Sticks and fists were the main causes, with the right eye and anterior segment frequently affected. Traumatic glaucoma and hypotony occurred in 66% and 34% of cases, respectively, with most managed medically (67%). Refractive errors affected 36 patients, predominantly myopic (75%). Initially, best-corrected visual acuity (BCVA) was commonly 6/60-6/18 (33.2%), improving at 6 months to 6/18-6/6 (49.5%). Common B-scan findings included vitreous hemorrhage (32%), traumatic cataract (19%), lens subluxation (13%), posterior vitreous detachment (9%), retinal detachment (8%), and lens dislocation (7%). Conclusion: Ocular injuries lead to multiple complications; they cannot be examined accurately by routine methods. B-scan ultrasonography is recommended while investigating these injuries this aids in the preparation of the surgery with an accurate understanding of the injury. Recommendation: Educating people, and creating awareness to adopt protective measures in the workplace can prevent the occurrence of blunt ocular trauma, and at the same time rapid diagnosis, early referral, accurate investigations, and appropriate management can prevent complications following trauma.